Validated LC Method for the Estimation of Dorzolamide HCl (Carbonic Anhydrase Inhibitor) in Ophthalmic Solutions - A. Narendra; D. Deepika; M. Mathrusri Annapurna (E-Journal of Chemistry)
A reverse phase HPLC method is described for the determination of Dorzolamide in eye drops. Chromatography was carried on an Inertsil ODS 3V column using Acetonitrile : (0.02M) 1,Octane Sulphonic acid buffer (pH 3.5) (36:64 v/v) on isocratic mode at a flow rate of 1 mL/min with UV detection at 254 nm. The detector response was linear in the concentration range 4-720 µg/mL. The limit of detection and limit of quantification are found to be 0.7041 and 2.3483 µg/mL respectively. The method was validated as per the ICH guidelines. The proposed method is rapid, accurate and precise and can be applied for the routine analysis of dorzolamide in ophthalimic solutions.